2006
DOI: 10.2109/jcersj.114.571
|View full text |Cite
|
Sign up to set email alerts
|

ポリカルボシランとナノ粒子によるメソポーラス炭化ケイ素の作製

Abstract: Mesoporous silicon carbide SiC ceramics were produced via the pyrolysis of polycarbosilane PCS with and without SiC nano sized particle filler, and their pore characteristics such as size and BET surface area were investigated. The amount of filler and the pyrolysis temperature significantly affected the surface area and pore size. The surface area of PCS reached around 0.5 m 2 g by the pyrolysis at 800c C and pore also was found to almost disappear. In contrast, the specimen with filler showed high surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…They attributed the well-developed sintering neck to the promotion of mass transfer by nano-powders. [17,18] On the other hand, high densities of stacking faults, interfaces and nano-pores [19,20] in nano-scale microstructures will enhance phonon scattering and reduce thermal conductivity. In this paper, thermal stability and properties of porous nano-SiC prepared from 600°C to 1,800°C are investigated.…”
mentioning
confidence: 99%
“…They attributed the well-developed sintering neck to the promotion of mass transfer by nano-powders. [17,18] On the other hand, high densities of stacking faults, interfaces and nano-pores [19,20] in nano-scale microstructures will enhance phonon scattering and reduce thermal conductivity. In this paper, thermal stability and properties of porous nano-SiC prepared from 600°C to 1,800°C are investigated.…”
mentioning
confidence: 99%
“…For the most part, the present samples have a full density of 3.003.05 g/cm 3 . This can demonstrate that controlled fine SiC grains for bi-modal SiC samples are crucial for obtaining improved mechanical properties.…”
Section: Resultsmentioning
confidence: 83%
“…The measured density of the green compacts is in the range of 1.621.90 g/cm 3 . The density of SC-F specimen showed relatively low value and its reason may be considered by agglomerates of fine SiC powders during compaction.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The pyrolysis temperature has significant effect on the shape and size of pores of the resultant ceramics [76][77][78][79]. It was demonstrated that the features of the produced ceramic foams were dependent on the composition and the structure of the pyrolyzed precursors.…”
Section: Sacrificial Templatementioning
confidence: 99%